Why Do Borrowers Make Mortgage Refinancing Mistakes? - Agarwal, Sumit; Rosen, Richard J.; Yao, Vincent (Management Science, 2016)
Refinancing a mortgage is often one of the most important financial decisions people make. Borrowers choose the interest rate differential at which to refinance, and when that differential is reached, they need to take the steps to refinance before rates change again. Using a simple closed-form solution approximation of the optimal refinancing rule and a unique panel data set including information from a large secondary market participant on refinancing, we find that approximately 57% of borrowers refinance suboptimally—50% choose the wrong rate, 17% wait too long to refinance, and 10% do both. Financially sophisticated borrowers make smaller mistakes, refinancing at rates closer to optimal and waiting less after mortgage rates reach their trigger rates. Evidence suggests borrowers learn from their refinancing experiences. This paper was accepted by Amit Seru, finance.